Laccase-13 Regulates Seed Setting Rate by Affecting Hydrogen Peroxide Dynamics and Mitochondrial Integrity in Rice - Yu, Yang; Li, Quan-Feng; Zhang, Jin-Ping; Zhang, Fan; Zhou, Yan-Fei; Feng, Yan-Zhao; Chen, Yue-Qin; Zhang, Yu-Chan (Frontiers in Plant Science, 2017)
Seed setting rate is one of the most important components of rice grain yield. To date, only several genes regulating setting rate have been identified in plant. In this study, we showed that laccase-13 (OsLAC13), a member of laccase family genes which are known for their roles in modulating phenylpropanoid pathway and secondary lignification in cell wall, exerts a regulatory function in rice seed setting rate. OsLAC13 expressed in anthers and promotes hydrogen peroxide production both in vitro and in the filaments and anther connectives. Knock-out of OsLAC13 showed significantly increased seed setting rate, while overexpression of this gene exhibited induced mitochondrial damage and suppressed sugar transportation in anthers, which in turn affected seed setting rate. OsLAC13 also induced H2O2 production and mitochondrial damage in the root tip cells which caused the lethal phenotype. We also showed that high abundant of OsmiR397, the suppressor of OsLAC13 mRNA, increased the seed setting rate of rice plants, and restrains H2O2 accumulation in roots during oxidative stress. Our results suggested a novel regulatory role of OsLAC13 gene in regulating seed setting rate by affecting H2O2 dynamics and mitochondrial integrity in rice.